The Effect Of Finding Decision , Profitabilityand Dividend Policy To Firm Value Of Consumer Goods Industry At Indonesia Stock Exchange In The Period Of 2012-2016 - Dwi Nur Sahid; Lis Zulifiati (Jurnal Ekonomi, 2019)
The purpose of this research is to determine whether the Funding Decision, Profitability Ratio, and Dividend Policy both individually and simultaneously affect significantly the firm value of the consumer goods industry in the Indonesia Stock Exchange (BEI) period 2012-2016.Funding Decision is represented by using Debt to Equity Ratio (DER), Profitability is represented by using Return On Equity (ROE), Dividend Policy is represented by using Devidend PayOut Ratio (DPR). By using purposive sampling technique, the sample used in this study amounted to 100 companies from the population of 20 companies and the period of research are 5 years. This causal-comparative research uses panel data with secondary data that collected by using documenting and archiving techniques from Indonesian Capital Market Electronic Library. Multiple regression estimation method from panel data used in this research is Fixed Effect Model. This research shows that Funding Decision (regression coefficient 5,419856), Profitability (regression coefficient -11,14584), and Devidend Policy (regression coefficient 0,468592) individually and silmutaneously affect the stock return of the consumer goods industry sector in the period of 2012-2016 significantly, with the value of Adjusted R2 is 0,940623.